Importation of dengue, Zika and chikungunya infections in Europe: the current situation in Greece. (May 2020) - Emmanouil, M.; Evangelidou, M.; Papa, A.; Mentis, A.
Abstract: Although several arboviruses—such as dengue (DENV), Zika (ZIKV) and chikungunya (CHIKV) viruses—are not endemic in Europe, they have the potential to emerge following importation of the virus, taking advantage of the favourable climate and ecosystem. DENV, ZIKV and CHIKV are transmitted by Aedes species mosquitoes and are amongst the most common travel-associated arboviruses. Furthermore, they are linked to sporadic, local outbreaks, especially in the southern parts of Europe. In this review we present in brief the DENV, ZIKV and CHIKV cases imported to Greece during the last 6 years (2013–2018), and we describe the recent laboratory data obtained from the Hellenic Pasteur Institute and the National Reference Centre for Arboviruses. We report 21 imported cases of DENV, ZIKV and CHIKV infections in travellers arriving in Greece. The probable origins were south-eastern Asian (71%) and north-central American (29%) countries. Furthermore, we stress the importance of early and accurate diagnosis in spite of a plethora of diagnostic challenges that clinicians and virologists have to face. Altogether, with the authorities' awareness and the preventive measures to be applied, local transmission events can be successfully avoided, especially in summer when the temperature is favourable for mosquito-borne infections.